2012
DOI: 10.1186/2045-7022-2-15
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of asthma in Portugal ‐ The Portuguese National Asthma Survey

Abstract: BackgroundAsthma is a frequent chronic respiratory disease in both children and adults. However, few data on asthma prevalence are available in Portugal. The Portuguese National Asthma Survey is the first nationwide study that uses standardized methods. We aimed to estimate the prevalence of current asthma in the Portuguese population and to assess the association between ‘Current asthma’ and comorbidities such as upper airways disease.MethodsA cross-sectional, population-based, telephone interview survey incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
2
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 34 publications
5
59
2
5
Order By: Relevance
“…The higher prevalence observed in the present study (29.8%) may reflect either a more accurate estimation of rhinitis in the elderly or an actual increasing tendency in rhinitis prevalence in this age group over the last years. A recent nationwide epidemiologic study performed in 2010 in Portugal, including individuals from all age groups and reporting rhinitis prevalence as a secondary aim, found that 22.1% of included subjects had rhinitis (21). However, direct comparisons are limited because different sampling and definitions for rhinitis were used.…”
Section: Discussionmentioning
confidence: 99%
“…The higher prevalence observed in the present study (29.8%) may reflect either a more accurate estimation of rhinitis in the elderly or an actual increasing tendency in rhinitis prevalence in this age group over the last years. A recent nationwide epidemiologic study performed in 2010 in Portugal, including individuals from all age groups and reporting rhinitis prevalence as a secondary aim, found that 22.1% of included subjects had rhinitis (21). However, direct comparisons are limited because different sampling and definitions for rhinitis were used.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that asthma affects about 6.8 to 10% of the Portuguese population [1][2] and only 57% of these are controlled. 3 Its global prevalence may reach 18% 4 and in 2004 the World Health Organization (WHO) estimated a total of 234 million individuals affected.…”
Section: Introductionmentioning
confidence: 99%
“…The study design has been described in detail elsewhere. 20 Briefly, to obtain a representative sample of the general population a two-stage cluster and stratified sampling design was used, including two steps. First, we selected a simple random sample of households within each municipality (stratum) using a list of landline telephone numbers; overall, 24,412 telephone numbers were selected.…”
Section: Methodsmentioning
confidence: 99%
“…The one we chose was associated with a higher specificity and lower asthma prevalence. 20 Repeated population surveys using representative, randomly selected samples of sufficiently large size, with similar questionnaires and definitions is the only way to provide comparable estimates of smoking and ETS exposure prevalence. 2 Methods to improve reporting accuracy (e.g.…”
Section: Limitationsmentioning
confidence: 99%